Polymorphism and danger susceptibility of system call DASTONs - Maarof, Mohd. Aizaini; Iqbal, Anjum (Springer Berlin / Heidelberg, 2007)
We have proposed a metaphor â€œDAnger Susceptible daTa codONâ€? (DASTON) in data subject to processing by Danger Theory (DT) based Artificial Immune System (DAIS). The DASTONs are data chunks or data point sets that actively take part to produce â€œdangerâ€?; here we abstract â€œdangerâ€? as required outcome. To have closer look to the metaphor, this paper furthers biological abstractions for DASTON. Susceptibility of DASTON is important parameter for generating dangerous outcome. In biology, susceptibility of a host to pathogenic activities (potentially dangerous activities) is related to polymorphism. Interestingly, results of experiments conducted for system call DASTONs are in close accordance to biological theory of polymorphism and susceptibility. This shows that computational data (system calls in this case) exhibit biological properties when processed with DT point of view.